Early defection of thyroid function disturbance on Norplant acceptor in goiter endemic area - Zainal Arifin Nang Agus, Zainal Arifin Nang Agus (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
In the surrroundings of mountainous area, many people are suffering from goiter due to low iodine contents in their diet. This study was aimed at examining T3, T4 and TSH concentration of the Norplant and IUD acceptors for 6 months. The acceptors were from an endemic goiter area in Cangkringan, Sleman, Yogyakarta. The results of this study showed that T3, T4 and TSH were in the normal range but relatively low level. Six months after using Norplant comparing with that using IUD, the T3 concentration decreased, while T4 and TSH concentration increased, but they were not significant (p>0,05). Based on those data, there was an evidence that after 6 months of using Norplant, the thyroid gland was hyperactive to produce tyroxine. After a long time period it would be a hyperplasia and hypertrophy of thyroid. Similar, further studies for a longer time are needed.Key words: Norplant - T3 - T4 - TSH - endemic goiter